Modulation of antitumor immunity with histone deacetylase inhibitors. (December 2017) - McCaw, Tyler R; Randall, Troy D; Forero, Andres; Buchsbaum, Donald J
Histone deacetylase inhibitors possess a broad array of antitumor activities; however, their net impact on the evolving antitumor immune response is highly dependent on the inhibitors used and the histone deacetylases they target. Herein, we sequentially focus on each stage of the antitumor immune response – from dendritic cell activation and migration, antigen uptake and presentation, T-cell activation and differentiation and the enactment of antitumor effector functions within the tumor microenvironment. In particular, we will discuss how various inhibitors have different effects depending on cellular activation, experimental design and specific histone deacetylases being targeted – and how these changes impact the outcome of an antitumor immune response. At last, we consider the impact these inhibitors may have on T-cell exhaustion and implications for combination with other immunomodulating therapies.